Analysis of Football Academy Students Skill: Using The David Lee Proficiency Test - Putri, Dhevana; Anam, Khoiril (Universitas Negeri Semarang, 2023)
Football is a popular team sport that is widely loved and played around the world. Basic football skills are crucial for every team member, and each individual must train in fundamental football techniques. Tests and measurements play a crucial role in football training as they can enhance players' skills. Safin Pati Sports School is a leading boarding football academy in Central Java, admitting students based on interest without any selection process. However, the students have not undergone any previous tests or measurements of their football skills. This research aims to analyze the level of basic football skills among students born in 2009 at Safin Pati Sports School. The research methodology employed purposive sampling technique, and a statistical descriptive analysis was conducted with 33 students born in 2009 as the research subjects. Data collection was carried out through the David Lee speed test. The results of the analysis indicate that the level of basic football skills among Safin Pati Sports School students is categorized as good, with 42.42% of students demonstrating good speed test scores. The positive outcomes are attributed to a well-designed program encompassing aspects of physical fitness, technical training, tactical drills, and mental exercises.